Student Dropout Trends and Causes in Higher Education: The Case of Kailali Multiple Campus - Madai, Tek Bahadur; Chand, Rajendra Bir; Sapkota, Shiba Prasad; Pant, Deepak Raj (KMC Journal, 2025)
This study examines the present situation and major causes of student dropout in higher educational institutions. Kailali Multiple Campus located in Kailali district of Nepal was selected for the study. The study utilized a quantitative research approach with a descriptive case study research design. Secondary and primary data were applied to analyze the trends of dropout and the influencing factors behind it. The secondary data source was students’ enrollment and presence in the campus final examination record; primary data were collected from the dropout students using a structured questionnaire. The study’s findings demonstrated that compared to programmes like MBA, BALLB, BBA, BBM and B.Sc. CSIT, students drop out from general programmes like BBS, BA and B.Ed. are more frequent. The study found the primary cause of student dropout is weak economic conditions. Additionally, the survey of the dropout students shows that the majority of dropout students had been getting ready to travel abroad. The implication of this research consists of providing crucial perspectives for policymakers in education, aiding establishments in enhancing academic and infrastructure standards, encouraging community engagement and directing students’ choices.